Poly(vinylidene fluoride)-Based Membranes for Microalgae Filtration - Marbelia, L. (Wiley-VCH Verlag, 2018)
Two poly(vinylidene fluoride) (PVDF) membrane modification approaches, i.e., poly(vinylpyrrolidone) (PVP) modification and sulfonation, were applied and investigated to produce a fouling-resistant membrane for microalgae filtration. Both methods were able to alter the membrane surface to become more hydrophilic. However, clean water permeance increased only for the PVP-modified membranes, while the sulfonated membranes underwent a significant morphology transformation to a denser membrane and thus lower permeance. Microalgae filtration with PVP-modified membranes showed less fouling compared to the pristine one, particularly in the beginning of the filtration, indicating that fouling reduction on these membranes mainly occurs in the initial fouling stage. Fouling is also found to be influenced by the microalgae species, possibly due to the different properties of the formed cake layer. Â© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim